An Assessment of Patient Satisfaction With Home Care Services in an Eastern City of Turkey - Yarasir, Ezgi; Bulut, Irem (Wiley, 2025)
AimThe aim of this study was to examine the socioeconomic characteristics of patients who are receiving home care in an eastern city of Turkey, assess how satisfied they are with these services and determines the factors affecting their level of satisfaction. DesignA quantitative descriptive and cross-sectional study design was used. MethodsFrom July to August 2022, a sample of 306 patients who were receivers of home care services participated in the research. The study comprised of a 'Personal Information Form' and the 'Home Health Care Services Patient Experience Questionnaire' supplied by the Turkish Ministry of Health, Department of Quality, Accreditation, and Employee Rights. The questionnaire evaluates the degree of satisfaction with home care services. The statistical analysis was performed using the SPSS 22.0 software. A significance level of p < 0.05 was utilised to determine statistical significance. ResultsOut of all the participants, 51.3% were female and the average age was 74.1 +/- 14.4 years. An impressive 92.8% of participants expressed their satisfaction with the home care services provided by the Ministry of Health, considering it highly effective. The mean satisfaction score of the participants in home care was determined to be 4.7 +/- 0.3. The study found that participants who had completed at least a high school education, were part of large families, had a high monthly income and perceived their health as poor reported significantly greater levels of satisfaction with home care services (p < 0.05). Patient or Public ContributionThe term patient satisfaction remains of significant importance in the professions of nursing and health services alike. The results of our study indicated that nearly all of the participants expressed that they were satisfied with their use of home care. Using regular satisfaction surveys is advised to determine the underlying reasons for dissatisfaction among patients who are unsatisfied with the service, and to conduct research with the goal of implementing improvements.
Keywords: health status; home care services; nursing; patient satisfaction; patients